Stability estimates for linear stochastic systems with deviating argument of neutral type - Bychkov, A. S.; Khusainov, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study linear stochastic differential equations with deviating argument of neutral type and establish sufficient conditions of stability. The functions determining the initial perturbations of solutions are found.